Impact of Personality Match/Mismatch on Employee Level Performance Which Ultimately Affects Organizational Performance (Global Journal of Management and Business Research, 2012)
The quality of the relationships employees have with each other determines the quality of the work outcomes. Personality of employees effects their roles and responsibilities in the organization. However, personality match between employee/employer has a strong impact on the interaction and communication patterns of the employees, as well as the subjective experiences of individuals which results in different forms of organizational integration and also in managing the interrelationships synergistically. On the other hand, every good employee that an organization fails to retain, walks out the door costing the business money, every poor or mismatched recruit can result in missed opportunities and can severely damage your culture and organizational reputation. Our paper is about how personalities matter in work environments and ultimately results in superior organizational performance. Too much difference among personalities at the work place creates difficulty in retaining employees. Mismatch can cause coordination problems. While matching personalities complement each other which lead to motivation at work place. We propose that personality match leads to positive attitudes. Furthermore, it creates emotional alignment at employee level, which contributes to increased organizational performance; develops emotional integration and a deep collaborative culture. Once all these factors are established the whole organization creates fit or connectedness which of course complements other aspects of emotional integration, collaborative culture and positive attitudinal alignment.